EFEKTIVITAS METODE MUROJA’AH DALAM MENGHAFAL AL-QURAN PADA SISWA DI SEKOLAH ARUNSAT VITTAYA SCHOOL PATTANI THAILAND - Faishol, Riza; Warsah, Idi; Mashuri, Imam; Sari, Novita (FKDP (Forum Komunikasi Dosen Peneliti), 2021)
This study aims to find out the implementation of muroja'ah method in memorizing the Qur'an in students at Arunsat Vittaya School Pattani Thailand; to find out the effectiveness of muoja'ah method in memorizing the Qur'an to students at Arunsat Vittaya School Pattani Thailand; to determine the supporting factors and inhibitions of the implementation of muroja'ah method in memorizing the Qur'an in students at Arunsat Vittaya School Pattani Thailand; to find out the solution to the factors inhibiting the muroja'ah method in memorizing the Qur'an in students at the Arunsat Vittaya School Pattani Thailand. The research method used is qualitative descriptive research. The data sources in this study include primary and secondary sources. Data collection is done by observation techniques, interviews and documentation. Data analysis is done using data reduction, data presentation, conclusion drawing. The validity of the data is obtained through triangulation methods. From the results of the study can be concluded that the implementation of memorization of the Qur'an using the muroja'ah method is to use a half-day half-glass/page system. Forms of memorization activities of the Qur'an include: depositing new/old memorization to teachers, muroja'ah pairs, exams memorizing the Qur'an. The muroja'ah method at Arunsat Vittaya School is considered effective because it sees the results of memorization of good students. This is seen from the results of tests, sima'an and trials conducted by researchers. Supporting factors of memorizing the Qur'an with muroja'ah method include: motivation, have a target, muroja'ah with friends used in prayer readings, with murrottal casset or MP3. Factors inhibiting the implementation of memorization of the Qur'an with muroja'ah method include: when there is a sense of saturation, drowsiness and lazy, forgetting the verses that have been memorized, many tasks from school and fatigue, home at home. Solutions in overcoming the factors inhibiting the implementation of muroja'ah method in Arunsat Vittaya School include: motivation, istiqomah in muroja'ah, time management.